Review of utilisation of obstetric high dependency care beds in a newly designed labour suite. (7th June 2011) - Rajagopal, R; Naz, A; Gibson, J; Roberts, J; Davidson, I
Abstract : Background: Confidential Enquiries into Maternal Deaths have recommended provision of a dedicated on-site obstetric high dependency unit for safer birth.1 Aim of the study: To analyse the utilisation of two high dependency care (HDC) beds in our purpose built labour suite delivering approximately 6000 pregnancies per annum. Material and methods: Retrospective study of admissions to HDU was undertaken for a period of 8 months from April 2010. Results: 74 admissions to HDU (1.8% of 3956 deliveries). 50 case notes (67.5%)were available for study analysis. 6 (12%)were antenatal admissions and 44 (88%) were postnatal admissions. Commonest indications for admission were: severe pre-eclampsia 11 (22%), massive haemorrhage 22 (44%)and medical disorders in 17 (34%), predominantly cardiac disease. In 31 (62%)the length of stay was <1 day, 15 (30%) between 1 to 2 days and in 4 (8%)it was > 3 days. 2 (4%)were transferred to ITU and 2 (4%) were re-admitted to HDU. Conclusion: The admission rate to our HDU facility was 1.8%. This and case mix are comparable to other studies. Mean length of stay was 2.75 days. Further analysis of our data will critically assess the level and intensity of senior clinical input into HDU patient care and guide creation of exit criteria, to potentially reduce length of stay without increasing the re-admissions rate. The results will assist our work force planning and staff training. The very low proportion of women requiring transfer to ITU suggests successful utilisation of this facility, 2 and benefits mother-baby bonding.